If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 3y * -2x Reorder the terms for easier multiplication: 4x = 3 * -2y * x Multiply 3 * -2 4x = -6y * x Multiply y * x 4x = -6xy Solving 4x = -6xy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6xy' to each side of the equation. 4x + 6xy = -6xy + 6xy Combine like terms: -6xy + 6xy = 0 4x + 6xy = 0 Factor out the Greatest Common Factor (GCF), '2x'. 2x(2 + 3y) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(2 + 3y)' equal to zero and attempt to solve: Simplifying 2 + 3y = 0 Solving 2 + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3y = 0 + -2 3y = 0 + -2 Combine like terms: 0 + -2 = -2 3y = -2 Add '-3y' to each side of the equation. 3y + -3y = -2 + -3y Combine like terms: 3y + -3y = 0 0 = -2 + -3y Simplifying 0 = -2 + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 3x^2-3=125 | | 18.42x-12.75=(5.32x-6.81)3.46 | | 7-9x-5-5x=4 | | 8(3x-4)=96 | | 3(2x+1)-3x=18 | | 11=-6x-5 | | 3x(14-9)+10= | | 5(6)-7(-7)= | | 2.8r=-5g | | 2a^2=24a | | -6=(.5)n-10 | | (x-3)*6+1=65 | | 2(x+3)/3+7/3=5(x-12)-2/3 | | 6(j-4)+j=-8 | | -10n+24+24n=-6n+24 | | 4x-8-3x=6x-2 | | -7x^2-5x+8=0 | | .44x+.25=.55x-.50 | | 18.42x-12.75=(5.32x-6.91)3.46 | | 1x+4=-8 | | 2-5x=-18 | | m^2-3m=10 | | 4x-2-3= | | 39+3x-12= | | 5y-3(2y-4)=8 | | c=5p+215 | | -19(z+2)+6(4z-4)=4(z-4)+11 | | -25=-5 | | (x-3).6+1=65 | | 2x^2-8x-5=0 | | 5y=10x+25 | | 10(5x+2)-3x=349 |